2016
DOI: 10.1162/jocn_a_00980
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Divided Attention in Natural Scenes

Abstract: Individuals are able to split attention between separate locations, but divided spatial attention incurs the additional requirement of monitoring multiple streams of information. Here, we investigated divided attention using photos of natural scenes, where the rapid categorization of familiar objects and prior knowledge about the likely positions of objects in the real world might affect the interplay between these spatial and nonspatial factors. Sixteen participants underwent fMRI during an object detection t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 74 publications
(99 reference statements)
1
7
0
Order By: Relevance
“…The current study aimed at characterizing large-scale brain networks supporting divided attention by re-analyzing previously reported fMRI data (Santangelo et al, 2010 ). Consistent with standard fMRI analyses reported by the previous literature (Fagioli and Macaluso, 2009 , 2016 ; Santangelo et al, 2010 ; Santangelo and Macaluso, 2013a ), the current study found that divided attention was sustained by regions belonging to the frontal and parietal cortices. However, the current data-driven approach based on ICA and CGA also revealed novel findings compared to the previous literature.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study aimed at characterizing large-scale brain networks supporting divided attention by re-analyzing previously reported fMRI data (Santangelo et al, 2010 ). Consistent with standard fMRI analyses reported by the previous literature (Fagioli and Macaluso, 2009 , 2016 ; Santangelo et al, 2010 ; Santangelo and Macaluso, 2013a ), the current study found that divided attention was sustained by regions belonging to the frontal and parietal cortices. However, the current data-driven approach based on ICA and CGA also revealed novel findings compared to the previous literature.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has demonstrated that monitoring of multiple streams of information typically results in a decrement of processing efficacy (Shaw and Shaw, 1977 ; Eriksen and St. James, 1986 ; Castiello and Umiltà, 1990 , 1992 ; Müller M. M. et al, 2003 ; Müller N. G. et al, 2003 ). At a neurophysiological level, divided attention was shown to recruit high-level brain regions, such as the dorsal frontoparietal attention network (Fagioli and Macaluso, 2009 , 2016 ; Santangelo et al, 2010 ), showing modulatory effects on sensory cortices deputed to process the incoming, multiple information (McMains and Somers, 2004 , 2005 ; Sreenivasan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, visual search in composite natural situations can be remarkably fast and efficient despite the overwhelming amount of information [96,97]. Fagioli & Macaluso [98] recently suggested that two factors may influence attentional control in these contexts. First, real-world objects are recognized more quickly when they are familiar object, a phenomenon termed “ultra-rapid categorization” [99].…”
Section: Discussionmentioning
confidence: 99%
“…The division of attention between the auditory and visual domains activates similar brain regions as directed attention tasks in each modality, but the activation of these regions is significantly reduced when cognitive resources are divided between the two modalities ( Castiello and Umiltà, 1990 , 1992 ; Eriksen and St. James, 1986 ; Hopfinger et al, 2000 ; Johnson and Zatorre, 2006 ; Loose et al, 2003 ; Müller et al, 2003a ; Müller et al, 2003b ; Salo et al, 2015 ; Shaw and Shaw, 1977 ), suggesting resource processing limitations ( Alais et al, 2006 ; Klingberg, 1998 ; Mowbray, 1953 ; Pashler, 1994 ; Roland and Zilles, 1998 ; Welford, 1952 ). In addition to these decreased activations during divided attention, there is also generally concurrent activation in components of the dorsal frontoparietal attention network ( Corbetta et al, 2008 ; Corbetta and Shulman, 2002 ; Fagioli and Macaluso, 2009 , 2016 ; Hopfinger et al, 2000 ; Johnson et al, 2007 ; Johnson and Zatorre, 2006 ; Loose et al, 2003 ; Moisala et al, 2015 ; Nebel et al, 2006 ; Salo et al, 2015 , 2017 ; Santangelo et al, 2010 ; Schubert and Szameitat, 2003 ; Stelzel et al, 2006 ; Vohn et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%